1989
DOI: 10.1139/e89-036
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of fracture styles in two granite bodies of the Superior Province

Abstract: A quantitative comparison is made between fracture styles in two late Archean granite intrusions of the Superior Province—–the Lac du Bonnet Batholith (LDBB) and Eye–Dashwa Pluton (EDP). These intrusions have a similar geological setting, similar mineral and chemical composition, and similar physical properties but vary markedly in volume (LDBB = 9060 km3; EDP = 122 km3).The fracture style of the LDBB consists of mainly low-angle thrust faults within otherwise poorly fractured granite. Subvertical fractures ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Other sparsely fractured granites have similarly low permeability, including the Carnmenellis batholith, for which Pine and Ledingham (1984) calculated a permeability on the order of 10 -17 m 2 between 1,500 and 2,000 m depth, and the Lac du Bonnet batholith, in which Stevenson et al (1996) found permeabilities between 3x10 -17 m 2 and 2.5x10 -22 m 2 in domains of sparsely fractured rock. Not all granite bodies are sparsely fractured; fracture intensity and style can be related to emplacement history and rate of cooling with small plutons experiencing greater amounts of brittle deformation than large (Stone et al 1989 instead mean values throughout the 9 km borehole are 7x10 -20 m 2 with a log standard deviation of 1.2 (Huenges et al 1997). In situ tests in the Lac du Bonnet URL and the Korean Underground Research Tunnel (KURT) give matrix permeability values between 10 -22 m 2 and 10 -20 m 2 for granitic rock (Martino and Chandler 2004;Cho et al 2013); laboratory tests on samples of the Grimsel granodiorite give values on the order of 10 -20 m 2 to 10 -19 m 2 (Schild et al 2001).…”
Section: Deep Borehole Disposal Safety Analysis 78mentioning
confidence: 99%
“…Other sparsely fractured granites have similarly low permeability, including the Carnmenellis batholith, for which Pine and Ledingham (1984) calculated a permeability on the order of 10 -17 m 2 between 1,500 and 2,000 m depth, and the Lac du Bonnet batholith, in which Stevenson et al (1996) found permeabilities between 3x10 -17 m 2 and 2.5x10 -22 m 2 in domains of sparsely fractured rock. Not all granite bodies are sparsely fractured; fracture intensity and style can be related to emplacement history and rate of cooling with small plutons experiencing greater amounts of brittle deformation than large (Stone et al 1989 instead mean values throughout the 9 km borehole are 7x10 -20 m 2 with a log standard deviation of 1.2 (Huenges et al 1997). In situ tests in the Lac du Bonnet URL and the Korean Underground Research Tunnel (KURT) give matrix permeability values between 10 -22 m 2 and 10 -20 m 2 for granitic rock (Martino and Chandler 2004;Cho et al 2013); laboratory tests on samples of the Grimsel granodiorite give values on the order of 10 -20 m 2 to 10 -19 m 2 (Schild et al 2001).…”
Section: Deep Borehole Disposal Safety Analysis 78mentioning
confidence: 99%
“…Subsequent brittle deformation occurred associated with later tectonic events (1.7 to 1.6 Ga and 1.1 to 0.9 Ga), and recent glaciation (< 1 Ma) has resulted in crystalline basement outcrops and thin (<25 m) Quaternary sedimentary deposits of variable thickness and extent (SKB 2008). Crystalline basement with similar history exists within the United States (for instance at the southern margin of the approximately 2-Ga-old Superior Craton in Minnesota and Wisconsin (e.g., Stone et al 1989), and can be reasonably expected to have similar hydraulic properties.…”
Section: Crystalline Host Rockmentioning
confidence: 99%
“…The Lac du Bonnet Batholith (LDBB) is one of many late to post-tectonic granites emplaced in the western Superior Province, towards the end of the 2760-2670 Ma Kenoran event (McCrank et al 1981;Stone et al 1989). It is a relatively undifferentiated and partly foliated porphyritic granite -granodiorite consisting, like many other Archean batholiths, of broadly related but not sequentially fractionated intrusions (Cerny et al 1987).…”
Section: Regional Setting and General Geologymentioning
confidence: 99%
“…Rock units range from a uniform grey to red or pink where altered. Most reddening is associated with fractures, where the rock has been subject to long-term exposure to groundwater, and cuts across rock unit boundaries Stone et al 1989). Lowtemperature alteration overprints the higher temperature forms around of the major low-dipping fracture zones.…”
Section: Regional Setting and General Geologymentioning
confidence: 99%